1993
DOI: 10.1006/cbmr.1993.1038
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Students' Use of MEDLINE

Abstract: MEDLINE search transcripts by a class of third-year medical students were analyzed. The 184 students were divided into three groups according to their search experience in terms of the number of sessions logged at the time of a search assignment. A strong relation was found between the level of search experience and the frequency of use in the subsequent 5 months. Over 80% of the students were able to retrieve a few useful items for an emergency clinical situation. More experienced searchers were able to retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
5
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 0 publications
0
26
5
1
Order By: Relevance
“…One possible solution is to identify the user characteristics and their relationship with system features that may contribute to better search performance. However, previous research on the impact of user characteristics in the use of information retrieval systems has suggested that (a) domain knowledge or specific topic knowledge is not correlated with search outcome (Allen, 1991;Pao, Grefsheim, Barclay, Woolliscroft, McQuillan, & Shipman, 1993) and (b) search experience with databases cannot predict search outcome (Fenichel, 1981;Howard, 1982;Sutcliffe, Ennis, & Watkinson, 2000). That raises the question in what specific conditions these system features like human-developed index terms and automatic indexing techniques will be useful for different kinds of users.…”
Section: Problem Statementmentioning
confidence: 98%
See 3 more Smart Citations
“…One possible solution is to identify the user characteristics and their relationship with system features that may contribute to better search performance. However, previous research on the impact of user characteristics in the use of information retrieval systems has suggested that (a) domain knowledge or specific topic knowledge is not correlated with search outcome (Allen, 1991;Pao, Grefsheim, Barclay, Woolliscroft, McQuillan, & Shipman, 1993) and (b) search experience with databases cannot predict search outcome (Fenichel, 1981;Howard, 1982;Sutcliffe, Ennis, & Watkinson, 2000). That raises the question in what specific conditions these system features like human-developed index terms and automatic indexing techniques will be useful for different kinds of users.…”
Section: Problem Statementmentioning
confidence: 98%
“…Domain knowledge or specific topic knowledge is not correlated to search outcome (Allen, 1991;Pao et al, 1993);…”
Section: User Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analisaram, também, a performance dos alunos por meio de questionários. Já Pao e col. 10 (1993), em avaliação do desempenho de alunos no acesso a bases de dados, colocam que a maioria das bibliotecas acadêmicas, principalmente da área da saúde, promovem de alguma forma o acesso a bases de dados e que o treinamento de usuários para esse fim tem sido prática comum desde a década de 80. …”
unclassified